Genome-wide Annotation and Comparative Analysis of Long Terminal Repeat Retrotransposons between Pear Species of P. bretschneideri and P. Communis - Yin, Hao (Sci Rep, 2015)
Recent sequencing of the Oriental pear (P. bretschneideri Rehd.) genome and the availability of the draft genome sequence of Occidental pear (P. communis L.), has provided a good opportunity to characterize the abundance, distribution, timing, and evolution of long terminal repeat retrotransposons (LTR-RTs) in these two important fruit plants. Here, a total of 7247 LTR-RTs, which can be classified into 148 families, have been identified in the assembled Oriental pear genome. Unlike in other plant genomes, approximately 90% of these elements were found to be randomly distributed along the pear chromosomes. Further analysis revealed that the amplification timeframe of elements varies dramatically in different families, super-families and lineages, and the Copia-like elements have highest activity in the recent 0.5 million years (Mys). The data also showed that two genomes evolved with similar evolutionary rates after their split from the common ancestor ~0.77–1.66 million years ago (Mya). Overall, the data provided here will be a valuable resource for further investigating the impact of transposable elements on gene structure, expression, and epigenetic modification in the pear genomes.